2015
DOI: 10.3892/mco.2015.685
|View full text |Cite
|
Sign up to set email alerts
|

Connexin subtype expression during oral carcinogenesis: A pilot study in patients with oral squamous cell carcinoma

Abstract: Abstract. Gap junctional intercellular communication (GJIC) and connexin (Cx) expression were reported in association with carcinogenesis in various types of tumours. In an earlier histomorphometric study, the protein levels of Cx subtypes 26, 43 and 45 were differentially expressed in oral squamous cell carcinoma (OSCC), corresponding lymph node metastases and dysplasia-free oral mucosa. Moreover, membrane Cx43 acted as an independent prognostic marker in OSCC tissues. This study aimed to confirm the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…connexin 43 (cx43), a member of the connexins family, is most abundantly expressed in the cardiac muscle (7). cx43 has been demonstrated to serve a role in a number of diseases, including oral squamous cell carcinoma, pancreatic cancer, prostate cancer, acute myeloid leukemia, myocardial edema, vascular restenosis and Parkinson's disease (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). cx43 is primarily a fast, low-resistance pathway that regulates electrical conduction between cardiomyocytes, coordinates mechanical and electrical activities of cardiac muscle and controls the conduction velocity of impulses to ensure that myocardial electromechanical activities are synchronized (18).…”
Section: Introductionmentioning
confidence: 99%
“…connexin 43 (cx43), a member of the connexins family, is most abundantly expressed in the cardiac muscle (7). cx43 has been demonstrated to serve a role in a number of diseases, including oral squamous cell carcinoma, pancreatic cancer, prostate cancer, acute myeloid leukemia, myocardial edema, vascular restenosis and Parkinson's disease (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). cx43 is primarily a fast, low-resistance pathway that regulates electrical conduction between cardiomyocytes, coordinates mechanical and electrical activities of cardiac muscle and controls the conduction velocity of impulses to ensure that myocardial electromechanical activities are synchronized (18).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the higher frequency of the mutated G allele in the population identifies a population profile different from that described in countries such as Brazil for this SNP ( 18 ).…”
Section: Discussionmentioning
confidence: 69%
“…These results match those of Brockmeyer et al . in samples of OSCC patients ( 18 ). Studies in breast cancer showed that silencing Cx43 expression contributes to breast carcinogenesis, due to enhanced cell proliferation, lost cell polarity, misorientation of the mitotic spindle, and lost multilayer architecture of epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations